THE EFFECT OF ECONOMIC CHANGE AS A FACTOR OF TRIPARTITE CONSULTATION ON THE PERFORMANCE OF STATE CORPORATIONS IN KENYA - Nzioki, Susan (Asian Academic Research Journal of Social Sciences & Humanities, 2015)
The study sought to establish the effect of economic changes such as globalization, privatization and inflation on the performance of state corporations in Kenya. The study was carried out in Nairobi County in Kenya. Data was obtained through a descriptive survey design. The study involved 279 unionized employees of state corporations in the County. A structured questionnaire with Likert scale questions and an interview guide were administered to collect data from study subjects. Data was analyzed quantitatively and qualitatively by use of Statistical Package of Social Sciences (SPSS). The study found that economic change had insignificant effect on the performance of state corporations. This effect was linked by the fact that though some state corporations had been privatized and high rates of inflation experienced, the government had cushioned the corporations from being negatively affected. The study recommends the following strategies to future economic challenges: collective negotiation and rational agreement on salary increase, concerted efforts by all parties to increase productivity, future negotiations should be informed by research that takes into account increase in production and agreement by partners on a national recovery programme like freeze in salary reviews until economic stability is realized. More importantly, the existing national income differentials should be addressed faithfully by all stakeholders. The study was concentrated in unionized corporations and therefore cannot be generalized in the private sector and non-unionized state corporations. The findings will help the social partners to collectively handle economic challenges which inevitably face them for their prosperity and industrial peace.
Keywords: Economic change, performance, social partners, tripartite consultation.